RANCANGAN DAN IMPLEMENTASI SISTEM KEARSIPAN KELURAHAN PAKANSARI BERBASIS WEBSITE - Yuniar, Sylviana; Al-Ikhsan, Safaruddin H. (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
The Pakansari Village archive data media are only stored in the register book for each category. Even then, there is still a lot of data that is not stored or a lot of data is lost due to inadequate storage media. This situation becomes a problem for people who want to find data to check it. The purpose of this study was to build a website for archive data in Pakansari Village using the OOP method. The research method used is the waterfall. The design of the system has been carried out with the UML model so that it consists of context diagrams, use case diagrams, actuvuty diagrams, sequence diagrams, component diagrams, collaboration diagrams, deployment diagrams. The system has been built with the following modules: registration module, login module, blank add module, blank detail module, blank edit module, blank delete module, blank print module.